Disparities Influencing Functional Outcomes Between Rural and Urban Patients With Acute Stroke - Llanos-Leyton, Natalia; Pardo, Carlos; Pinilla-Monsalve, Gabriel D.; Arango, Akemi; Valderrama, Jaime; Pugliese, Isabella; Amaya, Pablo (Frontiers in Neurology, 2022)
Introduction There is scarce information in Latin America about factors related to stroke patient outcomes in rural areas compared to urban ones. Objective To evaluate functional outcomes of stroke code patients from rural and urban areas and their relationship with socioeconomic disparity. Methods Prospective cohort study included patients of urban, semi-urban, and rural origin with stroke code from a high complexity hospital in southwestern Colombia between 2018 and 2019. Demographic, clinical data modified Rankin at discharge, and 3-month follow-up were analyzed. The poverty index, barriers to health access and availability of ambulances by the municipality was assessed at an ecological level. Results Five hundred and fifty five stroke patients were registered, 21.2% from rural areas, 432 (77.98%) had an ischemic stroke. There were no significant differences in sociodemographic factors and medical background. Urban patients had lower reperfusion therapies rates (23.25%). Favorable mRS at discharge (<3) was higher in urban areas (63.03%) and mortality was superior in rural patients (13.56%). The ambulance rate in semi-urban and rural areas was as low as 0.03 per 100.000 inhabitants, the poverty index was 11.9% in urban areas vs. 23.3% in semi urban and rural areas. Conclusions Rural patients treated in our center were more likely to present with severe strokes and unfavorable mRS at hospital discharge and 3-month follow-up compared to urban, despite having similar risk factors. There is an inverse relationship, which is not related to the poverty rate or the percentage of people with barriers to access to health. There is a need for further studies that assess barriers inherent in rural patients and establish a regional stroke network.